Glacial Crooked Lake, Vestfold Hills, East Antarctica - Gore, D. B.; Pickard, J.; Baird, A. S.; Webb, J. A. (1996)
Glacial Crooked Lake was an ice-dammed impoundment in Vestfold Hills, East Antarctica, that had a volume of (250 ± 45) × 10 6 m 3 . The impoundment is inferred to have existed during deglaciation following the Late Holocene Chelnok Advance of Sørsdal Glacier. The dam released water incrementally, allowing the formation of four major series of shorelines with a maximum height of 24 m above the current lake level of 22 m asl. Water from Glacial Crooked Lake overflowed into Watts Lake downstream, allowing saltwater there to mix, dilute, and be transported to the sea via Ellis Rapids. In this way water in Watts Lake became fresh, and alluvial fans consisting of cobbles and boulders formed below Crooked Lake and Ellis Rapids.